A comparative study between Class-C and Class-B quadrature voltage-controlled power oscillator for multi-standard applications. (April 2020) - Mansour, Marwa; Zekry, Abdelhalim; Ali, Mohammed K.; Shawkey, Heba
Abstract: In this paper a 0.35 ​mW Class-C/B series coupling quadrature voltage-controlled power oscillator (S-QVCO) based on the coupling between two identical LC VCOs is presented. The S-QVCO is designed using a 130 ​nm CMOS technology and it is suitable for multi-standard applications. High quality factor inductor is designed using the two top metal layers to enhance the phase noise performance of the VCO, also an improved switching varactor is used to achieve dual bands. The proposed QVCO achieves tuning range of 28.2% from 2.3 to 3.07 ​GHz, and low phase noise of −119.2 dBc at a 1-MHz offset frequency from 2.7 ​GHz carrier. By biasing the proposed QVCO in class-C, the DC current is reduced to 0.35 ​mA compared to 1.48 ​mA in class-B from 1 ​V supply voltage. The minimum achieved Figure-of-Merit (FOM) equals −192 dBc/Hz and the maximum given output power is 6.5 dBm. The phase error between quadrature output signals is maximum of 0.25 ° . The occupied area of the proposed QVCO equals 0.34 m m 2, while the total chip area including RF pads is 1 m m 2 .